2021
DOI: 10.3390/nu13103460
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Hypothalamic Inflammation, Phoenixin, and Subsequent Precocious Puberty

Abstract: Recent studies have shown a rise in precocious puberty, especially in girls. At the same time, childhood obesity due to overnutrition and energy imbalance is rising too. Nutrition and fertility are currently facing major challenges in our societies, and are interconnected. Studies have shown that high-fat and/or high-glycaemic-index diet can cause hypothalamic inflammation and microglial activation. Molecular and animal studies reveal that microglial activation seems to produce and activate prostaglandins, neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 62 publications
0
11
0
1
Order By: Relevance
“…The mechanisms underlying this process have not been fully understood and include genetic, metabolic, environmental, geographic, and nutritional factors. Indeed, it has been reported that puberty can be influenced by adipose tissue, gastrointestinal function, adrenal androgen production, physical, and psychological stress [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying this process have not been fully understood and include genetic, metabolic, environmental, geographic, and nutritional factors. Indeed, it has been reported that puberty can be influenced by adipose tissue, gastrointestinal function, adrenal androgen production, physical, and psychological stress [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, for example, even though organised sports were halted, habitual exercise was increased, leading to an augmentation in the amount of daily physical activity among children and adolescents (23). However, many studies revealed a substantial decrease in physical activity during quarantine, internationally, due to restricted access to physical activity (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…The phoenixin expression in the hypothalamus was modulated by peripheral signals, such as hormones and fatty acids ( McLlwraith et al, 2018 ). It was speculated that diet could stimulate phoenixin secretion, act on GnRH neurons and induce subsequent activation of GnRH ( Valsamakis et al, 2021 ). It was reported that an intracerebroventricular (i.c.v.)…”
Section: Function Of Phoenixinmentioning
confidence: 99%